2020
DOI: 10.3389/fpsyg.2020.00695
|View full text |Cite
|
Sign up to set email alerts
|

The Empathic Brain of Psychopaths: From Social Science to Neuroscience in Empathy

Abstract: Empathy is a crucial human ability, because of its importance to prosocial behavior, and for moral development. A deficit in empathic abilities, especially affective empathy, is thought to play an important role in psychopathic personality. Empathic abilities have traditionally been studied within the social and behavioral sciences using behavioral methods, but recent work in neuroscience has begun to elucidate the neural underpinnings of empathic processing in relation to psychopathy. In this review, current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 119 publications
1
19
0
4
Order By: Relevance
“…Indeed, our findings could be informative for the planning of more targeted and effective intervention treatments, supporting the recent evidence that parental involvement in prevention and treatment programs is a critical factor in ensuring success in people of this stage [ 14 ]. Moreover, this study has also suggested that the planning of interventions focused on the improvement of self-control and affective empathy should be promoted [ 94 , 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our findings could be informative for the planning of more targeted and effective intervention treatments, supporting the recent evidence that parental involvement in prevention and treatment programs is a critical factor in ensuring success in people of this stage [ 14 ]. Moreover, this study has also suggested that the planning of interventions focused on the improvement of self-control and affective empathy should be promoted [ 94 , 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Empathic dysfunctions have been associated with diverse maladaptive manifestations of personality such as psychopathy, antisocial personality disorder, conduct disorder, violence, aggression, and criminality (Blair, 2005;Jolliffe & Farrington, 2004;Miller & Eisenberg, 1988;Reniers et al, 2011;van Dongen, 2020;van Langen et al, 2014). Previous metaanalyses reported small to moderate empathy deficits in violent, juvenile, and sexual offenders (Jolliffe & Farrington, 2004;Morrow, 2020;van Langen et al, 2014) as well as an association between antisocial outcomes and empathy in individuals with a history of physical abuse in childhood and externalizing features (Miller & Eisenberg, 1988).…”
Section: Dissociating Psychopathy and Antisocial Behavior: What Can Empathy Teach Us?mentioning
confidence: 99%
“…Impairments in functioning of the vmPFC is problematic as this brain region is associated with empathic processing and emotional expression [28,29], moral judgment, impulsivity, and linked to aggression and violent behavior [15,[30][31][32][33][34][35][36]. Empathic abilities are vital for social enhancement, social interactions and relationships, for our emotional and social life and moral judgment [37,38] and a deficit in empathic abilities could thus lead to a higher risk of violence [5]. Studies using functional neuroimaging (i.e.…”
mentioning
confidence: 99%